![\huge{\underline{\underline{\boxed{\sf{\purple{ǫᴜᴇsᴛɪᴏɴ}}}}}} \huge{\underline{\underline{\boxed{\sf{\purple{ǫᴜᴇsᴛɪᴏɴ}}}}}}](https://tex.z-dn.net/?f=%5Chuge%7B%5Cunderline%7B%5Cunderline%7B%5Cboxed%7B%5Csf%7B%5Cpurple%7B%C7%AB%E1%B4%9C%E1%B4%87s%E1%B4%9B%C9%AA%E1%B4%8F%C9%B4%7D%7D%7D%7D%7D%7D)
![If \: sinθ \: = \frac{a}{b} \: \\ then \: prove \: that \: (secθ + tanθ) = \sqrt{ \frac{b + a}{b - a} } If \: sinθ \: = \frac{a}{b} \: \\ then \: prove \: that \: (secθ + tanθ) = \sqrt{ \frac{b + a}{b - a} }](https://tex.z-dn.net/?f=If+%5C%3A+sin%CE%B8+%5C%3A++%3D++%5Cfrac%7Ba%7D%7Bb%7D++%5C%3A+%5C%5C++then+%5C%3A+prove+%5C%3A+that+%5C%3A+%28sec%CE%B8+%2B+tan%CE%B8%29+%3D++%5Csqrt%7B+%5Cfrac%7Bb+%2B+a%7D%7Bb+-+a%7D+%7D+)
Answers
Answered by
79
Solution:-
Given
We have to proof
Now take
Using Pythagoras theorem we will find Base(x)
Now we know that
Now take
Hence proved
Answered by
108
Answer:
Given :-
➙ sin =
Prove That :-
➙ (sec + tan
=
Solution :-
➤ L.H.S = (sec + tan
)
↪ +
↪
↪
↪
↪
↪
↪
↪
↪
➤ R.H.S
Similar questions